2008
DOI: 10.1002/term.68
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal tissue engineering using silk biomaterials

Abstract: Silks have been proposed as potential scaffold materials for tissue engineering, mainly because of their physical properties. They are stable at physiological temperatures, flexible and resist tensile and compressive forces. Bombyx mori (silkworm) cocoon silk has been used as a suture material for over a century, and has proved to be biocompatible once the immunogenic sericin coating is removed. Spider silks have a similar structure to silkworm silk but do not have a sericin coating. This paper provides a gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 108 publications
(132 reference statements)
0
66
0
6
Order By: Relevance
“…Materials such as collagen, alginate, hyaluronic acid, silk fibroin, chitosan and starch are among the most studied polymers with numerous advantages depending on the specific applications [5][6][7][8][9][10][11][12][13]. One of the most relevant benefits of using materials of natural origin is their biodegradability inside the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Materials such as collagen, alginate, hyaluronic acid, silk fibroin, chitosan and starch are among the most studied polymers with numerous advantages depending on the specific applications [5][6][7][8][9][10][11][12][13]. One of the most relevant benefits of using materials of natural origin is their biodegradability inside the human body.…”
Section: Introductionmentioning
confidence: 99%
“…I n addition to being used as sutures, silk fibers hold great potential as biomaterials for wound dressings, artificial ligaments, tendons, tissue scaffolds, microcapsules, and other applications (1)(2)(3). Silkworms are the current biological source of silk sutures, but spider silk fibers have superior mechanical properties that are ideal for procedures requiring finer sutures, such as ocular, neurological, and cosmetic surgeries (2,4,5).…”
mentioning
confidence: 99%
“…Silkworms can be cultivated en masse, but territorialism and cannibalism preclude spider farming as a viable manufacturing approach (2). Thus, there is great interest in developing an inexpensive, convenient, and reliable biotechnological approach that can be used to manufacture spider silk fibers as biomaterials (3,6).…”
mentioning
confidence: 99%
“…The steam sterilization process can be useful for silk fibroin films: several authors have applied moist heat sterilization whithout any appreciable fibroin alteration (16,17,(39)(40)(41). On the other side, Lawrence et al (25) observed that the sterilization with autoclave increased Silk II structure because hydrostatic pressure increases elastic modulus and then crystalline structure content; saturated vapor environment decreases the Tg of silk fibroin, that combined with high temperature increases fibroin chain movement.…”
Section: Discussionmentioning
confidence: 99%